The effect of personality traits and self-efficacy on academic performance among sutdents at a private university in Malaysia - Eileen, Kuah; Lee, Yi Ling; Teo, Ern Qi (2025)
The aim of this research is to study the effect of personality traits and self-efficacy on academic performance among students at a private university in Malaysia. Personality traits and self-efficacy may affect academic performance through openness to experience, conscientiousness, extraversion, agreeableness, emotional stability and self-efficacy among students. The researchers targeted undergraduate students from University Tunku Abdul Rahman (UTAR). Questionnaire has been distributed through Google Form. The researchers have successfully collected 377 responses. Statistical Package for Social Sciences (SPSS) Version 29 has been used to analyze and interpret the data collected for pilot study and full study. To test the significant relationship between the independent variables (openness to experience, conscientiousness, extraversion, agreeableness, emotional stability and self-efficacy), and dependent variable (academic performance), the researchers have used the Pearson Correlation Analysis, and Multiple Linear Regression Analysis. It has been found that all the independent variables (openness to experience, conscientiousness, extraversion, agreeableness, emotional stability and selfefficacy) have significant and positive relationships with the dependent variable (academic performance). The summary of major findings, implications of the study, limitations and recommendations of this study have been provided in this research. Keywords: Academic Performance, Openness To Experience, Conscientiousness, Extraversion, Agreeableness, Emotional Stability, Self-Efficacy Subject Area: BF698-698.9 Personality